Effects of thermotherapy associated with electrostimulation on perilaryngeal pressure pain thresholds and vocal tract discomfort symptoms in vocally healthy women - Fuentes Aracena, Christopher; Biermann Orizola , Christopher; Torres Yáñez , Constanza (Revista de Investigación en Logopedia, 2024)
The effects of absolute vocal rest, transcutaneous electrical nerve stimulation (TENS) and TENS-associated thermotherapy on perilaryngeal pressure pain thresholds (PPT) and the severity of vocal tract discomfort symptoms (VTDSi) in vocally healthy women were compared. Forty-two women participated and were separated into three groups that received different intervention modalities: G1, absolute vocal rest; G2, TENS; and G3, thermotherapy associated with TENS. Prior to the intervention, each participant underwent a vocal load task. PTTs were assessed before (T1) and after the vocal load test (T2), and after the intervention (T3). VTDSi were assessed at T2 and T3. In all three groups, the PPTs at T2 were significantly lower than those at T1, whereas at T3 these were elevated. This increase was greater in G3, compared to the other two groups. With respect to the VTDSi, in G1, the severity of some symptoms, such as dryness, was reduced significantly; while in G2 and G3, the severity of all the symptoms studied decreased significantly. There were differences in the reduction of pain, tightness, and lump in the throat between G2 and G3 (TENS + thermotherapy > TENS). In conclusion, thermotherapy associated with TENS showed greater efficacy in increasing PPT and reducing the severity of VTDS.
Keywords: Transcutaneous Electric Nerve Stimulation; Laryngeal Muscles; Pressure pain threshold